Analisis Kinerja Bundaran di Bundaran Nganjuk untuk Perencanaan Jalan Tol Kertosono – Kediri - R Endro Wibisono; Muhammad Shofwan Donny Cahyono; Adhi Muhtadi (Universitas Muhammadiyah Surabaya, 2020)
AbstractThe Adipura Nganjuk Roundabout is a pathway that often gets stuck due to being crossed by a railroad crossing. The location is close to Nganjuk Regency, Kediri Regency and Jombang Regency which are distribution points for the western and southern regions in East Java Province. Need to do a management in traffic engineering which includes the construction of toll roads from Nganjuk to Kediri, this roundabout does not get saturated. The purpose of this study is as a benchmark Traffic forecast forecasting is carried out for 6 years from 2019 to 2025. The research method uses a roundabout analysis using a manual Indonesian road capacity. Based on the results of forecasting calculations, the Adipura Nganjuk roundabout will be able to reduce the value of the degree of saturation by building the Kertosono-Kediri toll road to a DS value below 1 (one). In 2019 the DS is 0.77. While in 2021 DS decreased to 0.44 through the construction of the Kertosono-Kediri toll road. In 2025 DS increased again to 0.59, in 2030 DS = 0.84, and in 2035 again increased to 1.19 as vehicle growth. The solution is to count the number of vehicles and work on further traffic.Keywords: Traffic Performance, Degree of Saturation, Roundabout Intersection, Toll PlanningAbstrakBundaran Adipura Nganjuk adalah jalur yang sering terjadi macet karena berdekatan dengan perlintasan kereta api. Lokasinya berada dekat Kabupaten Nganjuk, Kabupaten Kediri dan Kabupaten Jombang adalah tempat distribusi perekonomian untuk wilayah barat dan selatan di Provinsi jawa Timur. Perlu dilakukan suatu manajemen dalam rekayasa lalu lintas berupa pembangunan jalan tol dari Nganjuk ke Kediri supaya bundaran tersebut tidak semakin jenuh. Tujuan penelitian ini adalah sebagai tolok ukur Peramalan kinerja lalu lintas dilakukan selama 6 tahun dari tahun 2019 hingga tahun 2025. Metode penelitian menggunakan analisis simpang bundaran menggunakan manual kapasitas jalan Indonesia. Berdasarkan hasil perhitungan peramalan, bundaran Adipura Nganjuk akan dapat menurunkan nilai derajat kejenuhan dengan membangun jalan tol Kertosono-Kediri menjadi nilai DS dibawah 1 (satu). Tahun 2019 DS adalah 0,77. Sedangkan tahun 2021 DS menurun menjadi 0,44 seiring pembangunan tol Kertosono-Kediri. Tahun 2025 DS meningkat kembali menjadi 0,59, Tahun 2030 DS = 0,84, dan Tahun 2035 kembali meningkat menjadi 1,19 seiring pertumbuhan kendaraan. Solusinya adalah membatasi jumlah kendaraan dan melakukan rekayasa lalulintas lebih lanjut.Kata Kunci: Kinerja lalu-lintas, Derajat Kejenuhan, Simpang Bundaran, Perencanaan Tol